2015
DOI: 10.1016/j.optlaseng.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving copper plating adhesion on glass using laser machining techniques and areal surface texture parameters

Abstract: a b s t r a c tGlass is a promising substitute substrate material being evaluated for electronic packaging technology. Improving the electroless copper plated layer adhesion of the glass is one of the most important considerations for development of the technology. An excimer laser (248 nm) was used for structured texturing of glass surfaces (to improve adhesion) by changing mask dimensions, laser operating parameters and overlapping pitch spacing, and therefore producing a range of micro-scale features. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…He et al [231] improved the adhesion of the electroless copper on the glass by roughening the surface by laser alation. The laser parameters, i.e.…”
Section: Laser Machining-assisted Electroless Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al [231] improved the adhesion of the electroless copper on the glass by roughening the surface by laser alation. The laser parameters, i.e.…”
Section: Laser Machining-assisted Electroless Depositionmentioning
confidence: 99%
“…The character of the energy density is cyclic and inhomogeneous across the beam profile resulting in a departure of the Sq value from the linear relationship.
Figure 33 Relationship between (a) energy density and Sq, (b) shots per area and Sq, and (c) repetition rate and Sq [231]. [Elsevier License Number – 5365280963394].
…”
Section: Adhesion Improvement Using Mechanical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…B. He et al found the relationships between the critical load and 3D roughness parameters Spc , Sq , Vvc , Sdq in the micro-connected structure, and gave application range of Spc , Sq , Vvc , Sdq [ 19 ]. Zeng et al combined the surface height probability density function, autocorrelation function and height parameters to evaluate the correlation of 2D and 3D roughness parameters to surface bearing capacity, friction and lubrication performance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In slightly more recent times, other science areas have caught up with the existence of areal parameters and their potential to help understand adhesion, with a range of S parameters being in the biomedical sciences used to measure the adhesion and proliferation of fibroblasts and bacterial strains [18] as well as soft tissue attachment to titanium abutments (noting that this work also considered profile parameters) [19]. In addition to being explored within civil engineering applications -again attempting to correlate surface topography to adhesion or concrete and epoxy layers [20]- [22] as well as steel-epoxy adhesion interfaces [23], and initial work on the bond strength of copper/glass [24].…”
Section: Introductionmentioning
confidence: 99%